Sizing and Optimization for Hybrid Central in South Algeria Based on Three Different Generators - Ammari, Chouaib (Center of Biomass & Renewable Energy, Diponegoro University, 2017)
In this paper, we will size an optimum hybrid central content three different generators, two on renewable energy (solar photovoltaic and wind power) and two nonrenewable (diesel generator and storage system) because the new central generator has started to consider the green power technology in order for best future to the world, this central will use all the green power resource available and distributes energy to a small isolated village in southwest of Algeria named â€œTimiaouineâ€. The consumption of this village estimated with detailed in two season; season low consumption (winter) and high consumption (summer), the hybrid central will be optimized by program Hybrid Optimization Model for Electric Renewable (HOMER PRO), this program will simulate in two configuration, the first with storage system, the second without storage system and in the end the program HOMER PRO will choose the best configuration which is the mixture of both economic and ecologic configurations, this central warrants the energetic continuity of village.Article History: Received May 18th 2017; Received in revised form July 17th 2017; Accepted Sept 3rd 2017; Available onlineHow to Cite This Article: Ammari, C., Hamouda,M., and Makhloufi,S. (2017) Sizing and Optimization for Hybrid Central in South Algeria Based on Three Different Generators. International Journal of Renewable Energy Development, 6(3), 263-272.http://doi.org/10.14710/ijred.6.3.263-272